Unmeasured and Unseen: Program Evaluation in Noncredit Workforce Education Programs at Community Colleges - Tesfamichael, Tiffany (ProQuest LLC, 2014)
As lifelong learning and workforce education grow increasingly more important in American life, the mission of community colleges is shifting more and more toward continuing education, certificate training, and workforce training. The lack of a standard set of indicators has led to a variety of approaches to the assessment of noncredit workforce education programs (NWEP) at community colleges. Absent a common and accepted set of quality indicators for NWEP and an accreditation process and authority to measure noncredit course quality and program-level outcomes, it is difficult for education consumers, educators, and businesses to compare program quality among community colleges or to benchmark programs for continuous improvement efforts. This study aims to help develop standardized metrics to evaluate, improve, and communicate outcomes for those taking NWEP courses. This study used a qualitative research design employing an online survey with 50 total workforce education practitioners who participated, and semi-structured follow-up interviews with a subsample of nine subjects to examine challenges experienced by two-year colleges in evaluating NWEP program effectiveness. Respondents reported that faculty adoption of assessment in NWEP was unchanged compared to the preceding five-year period. Findings showed the three most common methods of NWEP assessment were course evaluations, licensure exam results, and noncredit enrollment count. Findings were inconclusive about the rate of transition from noncredit to credit-based programs. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]